Sistem Pendukung Keputusan Penjurusan Siswa Dengan Metode Simple Additiveweighting (SAW) - Sri Siswanti, Pratiwi, Wawan Laksito YS (Jurnal Ilmiah SINUS, 2014)
One role of Decision Support Systems ( DSS ) in education is the decision-making process for the selection of majors that they support decision making by providing an alternative to the majors right decision for students, where the decision results can be used as material to assist in making decisions majors . The purpose of this research is to make the program placement of students with a DSS application method is Simple Additive Weighting ( SAW ) to try to help the school to expedite and facilitate the data processing by providing an alternative outcome majors majors, majors determination and class division majors. Because of all this is still in the process of computation using Microsoft Excel which requires a lot of time and effort in the process , also the results obtained are less accurate because it could have been a lot of mistakes there . This application uses the values of the criteria and limit values can be changed to pass the discretion of the school . With the results of the graduation status of each major option provided then processed to perform majors ranking results based on the criteria for the calculation of the total value of getting the right majors and is also capable of processing division major classes according quota provided pemrograman Delphi and MySQL as database . Â Keyword : Decision support systems, placement of students, simple additive weighting